The role of the CtIP gene as a genetic susceptibility factor for radiation leukaemogenesis - Nasilowska, A (2014)
Exposure to ionising radiation increases the risk of cancer, including acute myeloid leukemia (AML), which is the most common myeloid leukaemia. The C-terminal binding protein (CtBP)-interacting protein (CtIP), which is essential for embryonic development and possibly functions as a tumour suppressor, has been identified as a strong candidate for susceptibility to radiation-induced AML (rAML).